A longitudinal study of incident hypertension and its determinants in Indian adults aged 45 years and older: evidence from nationally representative WHO-SAGE study (2007–2015) - Bhatia, Mrigesh; Dixit, Priyanka; Kumar, Manish; Dwivedi, Laxmi Kant (Frontiers in Cardiovascular Medicine, 2023)
Objectives Hypertension (HT) is a leading cause of mortality and morbidity in developing countries. This study aimed to estimate the incidence of HT among adults aged 45 years and older in India and its associated risk factors. Methods This study used longitudinal data from the Indian sample of the first and second waves of the World Health Organization Study on Global Ageing and Adult Health (WHO-SAGE). A bivariate analysis using Pearson's chi-square test was done to examine the associations of individual, lifestyle, and household characteristics with HT status reported in Wave 2. Incident HT changes were analyzed by adjusting for various covariates in the generalized estimating equation (logit link function) with an exchangeable correlation matrix and robust standard errors. Results The study found that during the 8-year period from 2007 to 2015, the incidence of HT in individuals aged 45 years and over was 20.8%. Pre-hypertensive individuals had an overall incidence rate of 31.1 per 1,000 [95% confidence interval (CI): 26.20–35.9] and a 2.24 times higher odds ratio: 2.24 (95% CI: 1.65–3.03) of developing incident HT compared to those who were normotensive. Adults aged 45 years and older, overweight/obese individuals, and women were more at risk of incident HT. Conclusion One in five individuals had developed HT over 8 years, with a greater risk of incident HT among women than men. Pre-hypertensive individuals were at a greater risk of developing incident HT compared to normotensive individuals. The study recommends comprehensive and effective management of pre-HT to tackle the burden of HT.